2014
DOI: 10.1089/aid.2014.5465.abstract
|View full text |Cite
|
Sign up to set email alerts
|

Age-disparate Partnerships and Risk of HIV-1 Acquisition among South African Women Participating in the VOICE Trial

Abstract: A recent analysis from South Africa reported no association between age-disparate relationships and HIV-1 acquisition. We assessed the association between male partner age and HIV-1 acquisition among South African women participating in the VOICE trial. Of 4,077 women enrolled, 3,789 had complete data; 26% and 5% reported having a partner >5 and >10 years older at enrollment, respectively. Reporting a partner >5 years older (HR=1.00; 95% CI 0.74, 1.35) or >10 older (HR=0.92; 95% CI 0.49, 1.74) was not associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 14 publications
1
18
1
Order By: Relevance
“…Women in the current study were exposed to intensive HIV and STI risk reduction counselling during their study visits [33], but this appears to have had little or no impact on behavior change to reduce their risk of STIs and HIV infection, particularly in young women. As shown in this and other studies, young women continue to experience early age at sexual debut, use condoms inconsistently, engage in transactional sex, and tend to have sexual partners that are several years older than themselves [29,36,37]. Risky sexual behavior and HIV incidence rates, particularly in young cohorts in high HIV endemic areas like Southern Africa, have remained virtually unchanged for decades since the start of the HIV pandemic [2,[38][39][40], prompting the question 'what else do we need to end HIV/AIDS?'…”
Section: Discussionsupporting
confidence: 54%
“…Women in the current study were exposed to intensive HIV and STI risk reduction counselling during their study visits [33], but this appears to have had little or no impact on behavior change to reduce their risk of STIs and HIV infection, particularly in young women. As shown in this and other studies, young women continue to experience early age at sexual debut, use condoms inconsistently, engage in transactional sex, and tend to have sexual partners that are several years older than themselves [29,36,37]. Risky sexual behavior and HIV incidence rates, particularly in young cohorts in high HIV endemic areas like Southern Africa, have remained virtually unchanged for decades since the start of the HIV pandemic [2,[38][39][40], prompting the question 'what else do we need to end HIV/AIDS?'…”
Section: Discussionsupporting
confidence: 54%
“…13, 15 There are potential reasons for this discrepancy. Namely, the current sample focuses on a much younger cohort; therefore, the effects of partner age discordance may be more pronounced amongst younger women than those who are older.…”
Section: Discussionmentioning
confidence: 99%
“…13 Similarly, Balkus and colleagues (2014) reported that there was no association between partner age discordance and HIV incidence among South African women, even when stratified by age (aged 18-45 years). 15 Conflicting findings could be related to differences in outcomes examined considering that more recent studies focused on HIV incidence, while earlier studies focused on HIV risk behaviors. Though related, these outcomes are quite different.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While some cohort and phylogenetic studies provide evidence that age-disparate partnership increase young women’s risk of HIV acquisition,18–21 other cohort studies have found no association between age-disparate partnerships and HIV acquisition 22 23. One hypothesis following these null results is the possibility of reduced coital frequency, which has been posited as a potential characteristic of age-disparate partnerships that results from coital dilution: the reduction in frequency of sex acts per sexual partner as a result of concurrent partnering 24.…”
Section: Introductionmentioning
confidence: 99%